Mengukur Dampak Belanja Pemerintah Bidang Pendidikan Dan Kesehatan Terhadap Tingkat Kemiskinan Di Papua Barat - Marcus R. Maspaitella; Rully N. Wurarah; Henry A. Setiawan (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
Poverty is the main problem occurred in all developing countries, including Indonesia. Poverty rates in Indonesia are very various between provinces. Poverty alleviation also have strong association with the implementatation of programs and tasks derived from the government budgeding instument. This paper aims to analyse the influence of government spending on education and health on poverty rate in Papua Barat province. Sample in this research includes five regencies and one manicipality. Panel data regression was employed to estimate the fitted model. The results indicated that government spending on education has a significant influence on poverty reduction, meanwhile government spending on health has not been a significant driver for reducting the poverty rate. An important implication is that the the implementation of budgeting on education need to be increased by taking into account the effectiveness of its allocation, so that it is expected to connect with poverty alleviation through reducing unemployment and expanding job opportunities.